Containing Violence in El Salvador: Community Organization, Transnational Networks and State–Society Relations - Viviana García Pinzón (Development and Change, 2022)
Extant research has analysed the impact of security policies, truces and informal agreements on both the dynamics and traits of organized violence in El Salvador. However, less is understood about variation in the levels of lethal violence across subnational units. This article contributes to filling this gap. Based on a case study of the municipality of Chalatenango, the analysis shows that community organization and translocal dynamics are crucial to explaining violence containment. Local communities have managed to control the levels of lethal violence and deter criminal actors amid a national context characterized by state neglect and chronic violence. Community organization is not territorially bound but extends across transnational networks. Migrants are a source of livelihoods for the local population; they also contribute to providing public goods and participate in local forms of organization. Transnational networks have forged a migration corridor that enables immigration to the United States. In addition, community organization informally contributes to the capacity of the local state to perform its functions, thereby shaping cooperative state–society relations. This analysis sheds new light on the conditions shaping the variation in levels of violence at the subnational level and local governance dynamics.
Keywords: 300